ANALISIS STRUKTUR DAN DESAIN ORGANISASI DALAM OPTIMALISASI KINERJA PEGAWAI DI MTS SA NURUL HUDA - Aziz, Nur; Wulandari, Wulandari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study analyzes organizational structure and design in optimizing employee performance at MTs SA Nurul Huda, contributing to educational management development, especially in Islamic boarding schools. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation. The analysis followed the Miles and Huberman model, including data condensation, presentation, and conclusion drawing.Findings indicate that organizational structure and design significantly influence employee performance effectiveness. The alignment of organizational design with the school's vision, mission, and objectives emerges as a strategic factor. Key principles of organizational design directly affect performance, supported by factors such as school size, goals, strategies, culture, values, and external environment.Challenges identified include limited human resources, involving both teaching and administrative staff. Additionally, tasks outlined in job descriptions are often carried out by individuals with spare time rather than by those assigned, leading to inefficiencies.This research highlights the importance of strategically structured organizational design for performance optimization. The findings hold implications for improving management practices in Islamic boarding schools, providing insights into addressing challenges and enhancing the effectiveness of employee roles and responsibilities.